2020
DOI: 10.3390/nu12113421
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supplementation with Low Doses of a Cod Protein Hydrolysate on Satiety Hormones and Inflammatory Biomarkers in Adults with Metabolic Syndrome: A Randomized, Double-Blind Study

Abstract: Metabolic syndrome (MetS) is characterised by metabolic abnormalities that increase the risk of developing type 2 diabetes mellitus and cardiovascular disease. Altered levels of circulating ghrelin, several adipokines and inflammatory markers secreted from adipose tissue, such as leptin, adiponectin, tumor necrosis factor alpha, are observed in overweight and obese individuals. We assessed the effect of supplementation with low doses of a cod protein hydrolysate (CPH) on fasting and postprandial levels of acyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In this study, no differences were observed regarding the number of EECs GHR-IR in the experimental diets compared to the CTR. In overweight/obese individuals, Jensen et al [113] hypothesized that supplementation with cod protein hydrolysate for 8 weeks would have a suppressive effect on postprandial GHR levels. These potentially beneficial effects were hypothesized to occur due to the presence of small peptides, mainly di-and tripeptides, which are rapidly absorbed from the GI tract and may affect appetite regulation pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, no differences were observed regarding the number of EECs GHR-IR in the experimental diets compared to the CTR. In overweight/obese individuals, Jensen et al [113] hypothesized that supplementation with cod protein hydrolysate for 8 weeks would have a suppressive effect on postprandial GHR levels. These potentially beneficial effects were hypothesized to occur due to the presence of small peptides, mainly di-and tripeptides, which are rapidly absorbed from the GI tract and may affect appetite regulation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that fasting and postprandial concentrations of acylated GHR were not affected by 4 g of cod protein hydrolysate for 8 weeks. Jensen et al [113] reported the effect of low-dose cod protein hydrolysate supplementation on fasting and postprandial acylated GHR levels: they observed no effect on fasting or postprandial acylated GHR levels. On the other hand, a single dose of 20 mg/kg body weight of cod protein hydrolysate had no effect on postprandial acylated GHR levels or hunger-related sensations in comparison with the control group [33].…”
Section: Discussionmentioning
confidence: 99%
“…A series of trials that investigated the effects on body weight and TNF-α in overweight/obese participants following intervention with other bioactive (micro)nutrients have been examined [ 95 , 96 , 97 , 98 , 99 , 100 ] ( Table S4 ). The studies were primarily conducted in mixed populations of men adult men and women, with duration periods between 28 d and 90 d. The levels of protein were measured using an ELISA assay in serum [ 96 , 97 , 98 , 99 , 100 ], except for one study where the levels of TNF-α were measured in plasma [ 95 ]. The CV% values ranged from <10% in some cases up to 40–50% in several groups.…”
Section: Human Intervention Studies Looking At the Effects Of Foods A...mentioning
confidence: 99%
“…The data regarding the modulation of the levels of TNF-α were variable and the effect of the different treatments in comparison with the PLA yielded only (NS) results ranging from a reduction of −56 pg/mL with the mixture of leucine and vitamin B6 (NuFit) [ 95 ] to an increase of +0.61 pg/mL with the black soy peptide [ 97 ]. Intervention with a NuFit active blend (leucine and vitamin B6) [ 95 ], L-arginine [ 96 ], zinc [ 98 ], and hydrolysed cod protein [ 100 ] did not show any reducing effects on body weight. Whereas, body weight was significantly reduced following the intake of black soy peptide [ 97 ], and WC was also reduced with the intake of yeast β-glucan [ 99 ].…”
Section: Human Intervention Studies Looking At the Effects Of Foods A...mentioning
confidence: 99%